Vision and change in institutional entrepreneurship : the transformation from science to commercialization - Drori, Israel (Berghahn Books, 2011)
Sheltered for a long time within the public sector environment with high job security and professional research autonomy, defense R & D organizations faced unprecedented challenges when government support was being withdrawn and closure threatening. They needed to be led by a suitable vision in order to implement comprehensive changes to their operations and remain viable. This study explores this constitution of vision as a mechanism of intentional change, a strategic tool to reach the desired future for the organization. Going beyond the current literature, the authors ask to what extent, and.